An extended evaluation of schema issues advisor in the azure SQL database - Dunđerski, Dejan; Lazić, Stefan; Tomašević, Milo; Bojić, Dragan (Telfor Journal, 2018)
The analysis of the telemetry data in Azure SQL database has revealed that most of the problems affecting the customers are due to the schema inconsistency errors. An assumption has been made that direct e-mail notifications sent to the customers about the current problems could significantly shorten time to resolve them. The prospective benefits are first validated by sending e-mail recommendations manually. Then, in an iterative way, the schema issue advisor that detects anomalies and automatically sends the appropriate notifications to the customers is implemented on top of Azure resources. Finally, an extended evaluation has confirmed the expected benefits of direct communications with the customers.